Star Trek: Burden of Knowledge - Tipton, David; Tipton , Scott (IDW, 2014)
The next adventure of the classic Enterprise crew begins here! When a routine Federation diplomatic visit turns suddenly and unexpectedly violent, Captain Kirk, Mr. Spock and Dr. McCoy find themselves kidnapped and halfway across the galaxy! An Original Series-era miniseries from the creative team behind Spock: Reflections!